Efek akut dari latihan bersamaan dan pernapasan pada fungsi paru pada wanita sindrom pasca-covid-19 - Listiarini, Dian; Kushartanti, BM. Wara; Arovah, Novita Intan (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2023)
The incidence of persistent respiratory symptoms after acute post-COVID-19 infections, referred to as post-COVID-19 syndrome, is high. This study aimed to determine the feasibility and the acute effects of the combination of aerobic, strength and breathing exercises on pulmonary function and oxygen saturation among women post-COVID-19. This study involved 36 women post-COVID-19, with a mean age of 34.4±9.1 years, in a 45-minute aerobic, strength, and breathing exercise with an intensity of 65-75% maximum heart rate. The pulmonary function was measured with spirometry, while oxygen saturation was measured with an oximeter. These measurements were taken pre and post-exercise. Feasibility was determined as participants’ ability to complete the exercise and the incidence of adverse effects. A pair-t-test and effect size were assessed to estimate the acute effects of the exercise on Cohen’s d estimation. All patients complied, and no adverse events were reported, thus, supporting the feasibility of the exercise protocol. There was an increase in most post-exercise pulmonary function and oxygen saturation compared to pre-exercise (p <.001 to 0.03), with effect sizes ranging from 0.5 to 0.8, indicating medium to large effects of the exercise program on pulmonary functions and oxygen saturation. In conclusion, the combination of aerobic, strength, and breathing exercises is feasible and safe for women post-COVID-19 and potentially improves most pulmonary functions. Further research is recommended to evaluate the longer adaptation of the exercise on the pulmonary function in post-COVID-19.